(untitled) (Archive of Conferences, 2020)
This article mainly discusses the importance of toner in powder, which is widely used in printers, copiers, and printing houses. Today the number of printing houses in Uzbekistan exceeds 150. It follows from this that if the toners used for printing are not produced or purchased in sufficient quantities, the printing machines will stop working. This leads to unemployment, lack of access to the information people need, negative impact on the productivity of enterprises and organizations, and so on. However, it is believed that this product - toner - is mainly produced in several countries, and they vary in composition and quality